2000
DOI: 10.1159/000055286
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Isoform of the Progesterone Receptor cDNA in the Human Testis and Detection ofIts mRNA in the Human Uterine Endometrium

Abstract: A novel isoform (termed isoform S) of the progesterone receptor (PR) cDNA (PR isoform S cDNA) which consists of a previously unidentified 5’ sequence and exons 4–8 of the intracellular PR gene has been cloned from the human testicular cDNA library. The 5′ sequence of the message was confirmed to be derived from a novel exon (termed exon S) by genomic cloning. The expression level of the PR isoform S mRNA was higher in the spermatozoon than in the uterine endometrium with a lower expression level of the PR isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…A switch from one isoform of PR to another is yet to be confirmed in the cycling endometrium but could be evidence for the hypothesis that similar processes regulate menstruation and parturition through the ER-dependent regulation of PR isoforms. Recent data suggest that an additional isoform of PR (called PR-S) apparently exists in the endometrium that could be the surface PR isoform although to our knowledge, these data have yet to be confirmed (Hirata et al 2000). Indeed, using RT-PCR, we have been unable to confirm the presence of PR-S in our endometrial samples (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…A switch from one isoform of PR to another is yet to be confirmed in the cycling endometrium but could be evidence for the hypothesis that similar processes regulate menstruation and parturition through the ER-dependent regulation of PR isoforms. Recent data suggest that an additional isoform of PR (called PR-S) apparently exists in the endometrium that could be the surface PR isoform although to our knowledge, these data have yet to be confirmed (Hirata et al 2000). Indeed, using RT-PCR, we have been unable to confirm the presence of PR-S in our endometrial samples (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…Consequently, PR‐B is an activator of transcription and PR‐A is a transcriptional repressor 41,43‐45. In addition, there are several truncated forms of PR as well as splice variants that may have an impact on progesterone sensitivity 46‐51. Thus, the true tissue responsiveness to progesterone is dependent on the subtype and the expression level of the progesterone receptor.…”
Section: Progesterone Receptors and Their Role In “Functional” Progesmentioning
confidence: 99%
“…These include PR-S and PR-T originally cloned from a human testicular cDNA library with transcripts demonstrated in human endometrium (16,17). The transcripts are characterized by novel noncoding 5Ј exons (S, T) derived upstream of exon 1 of the nuclear PR followed by sequence for exons 4 -8.…”
mentioning
confidence: 99%